IMPACT OF PROPERTY CRIME ON SOCIOECONOMIC AND PSYCHOLOGICAL WELL-BEING OF VICTIMS IN WUKARI LGA OF TARABA STATE, NIGERIA - Abubakar, Ahmadu; Valentine Onyegbulem, Emeka (African Journal of Social and Behavioural Sciences, 2024)
Crime has registered its presence across society, thus depositing varying proportions of effects on victims. As crime exerts its toll on socioeconomic and psychological states of victims, it becomes expedient to interrogate its forms; and the level of damage it has caused to victims. This study aimed to assess the effects of property crime victimisation on victims’ socioeconomic and psychological conditions in the Wukari LGA of Taraba State. The objectives of the study were to assess the effect of property crime victimization on the socioeconomic condition of victims and to ascertain the effect of property crime victimization on post-traumatic stress disorder of victims. The survey design was adopted for the study. Questionnaires were used to collect primary data. The Cochran sample size determination formula was used to generate 385 samples. A multi-stage sampling technique was used to select respondents across clusters of settlements to complete the questionnaire. At the descriptive level, simple frequencies and percentages were used. Additionally, inferential statistics such as Chi-square tests and ANOVA were used to test the research hypotheses. The descriptive review revealed that, burglary crime was the most perpetuated form of property crime. Victims of property crime faced social, economic and psychological challenges. Poverty and financial loss, decreased investment, difficulty in forgetting scenes of attack and the development of intrusive memory, negative thinking and mood were devastating. The chi- square results (X 2=22.373, 12, P<.05) revealed that; property crime had a significant effect on victims’ socioeconomic status. Additionally, the ANOVA results revealed a significant effect of property crime on insomnia [F (3, 371) =3.704, P=0.012] and the loneliness and avoidance attitudes of victims [F (3,371) =2.849, P=0.037]. The study recommended financial and material compensation for victims of property crime, including counselling, improved security of lives and property and institutional measures to reduce unemployment and breach the poverty gap so that perpetrators of property crime would be kept at bay.